Influence of Cochlear Implantation on Vestibular Function in Children With an Enlarged Vestibular Aqueduct - Wang, Ruijie; Zhang, Daogong; Luo, Jianfen; Chao, Xiuhua; Xu, Jiliang; Liu, Xianfeng; Fan, Zhaomin; Wang, Haibo; Xu, Lei (Frontiers in Neurology, 2021)
Background: Cochlear implantation (CI) is becoming increasingly used in rehabilitation of hearing-impaired patients. Children with an enlarged vestibular aqueduct (EVA) need CI for severe or profound hearing loss, with excellent outcomes in hearing rehabilitation. However, vestibular function influenced by CI in children with EVA has not been clarified. We compared the characteristics of vestibular function in implanted children with EVA and those with normal cochlea. Methods: In this retrospective case-control study, 16 children with large vestibular aqueduct syndrome (LVAS) and 16 children with normal cochlea were recruited as the Study and Control Group, respectively. All children (mean age, 10.3 ± 4.4 years) had bilateral profound sensorineural hearing loss (SNHL) and normal pre-operative vestibular funcions, and underwent unilateral CI. Otolith and canal functions were assessed before CI and 12 months thereafter. Cervical vestibular-evoked myogenic potential (cVEMP), ocular vestibular-evoked myogenic potential (oVEMP), and video head impulse test (vHIT) were evaluated. Results: Full insertion of the electrode array was achieved in all the cases. Preoperatively, no significant differences on parameters in cVEMP between the Study and Control Group were revealed (p > 0.05). In pre-operative oVEMP, shorter N1 latencies (p = 0.012), shorter P1 latencies (p = 0.01), and higher amplitudes (p = 0.001) were found in the Study than in the Control Group. The Study Group had shorter P1 latency in cVEMP (p = 0.033), and had lower amplitude in oVEMP after implantation (p = 0.03). Statistically significant differences were not found in VOR gains of all three semicircular canals before and after surgery (p > 0.05). Pre- and post-implantation VEMP results revealed that the Control Group had significant deterioration rate after CI (p < 0.05). The surgical approach and electrode array had no statistically significant influence on the results of VEMP (p > 0.05). Conclusion: oVEMP parameters differed between children with EVA and normal cochlea before surgery. Systematic evaluations before and after cochlear CI showed that otolith functions were affected, but all three semicircular canals functions were essentially undamaged after implantation. In contrast to normal children, children with EVA are more likely to preserve their saccular and utricular functions after CI.